Test of Various PGR and Concentrations to Shoot Cuttings on Chrysant Plant (Dendranthema grandiflora T.) - Santoso, Mudji; Sitawati, Sitawati; Aprilia, Lia (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2016)
Chrysanthemum (Dendranthema grandiflora T.) seedling production in Indonesia is still limited, even still far from the requirement. Chrysanthemum is using shoot cuttings as propagation, it needs hormone to accelerate root growth and improve root quality that will ultimately improve the quality plants and fulfill the demand of this flowers. In this study, young coconut water and cow urine are alternative substitutions of synthetic plant growth regulator. The research was conducted in screenhouse which is using plastic UV as roof, at Sidomulyo, Malang with the altitude 700 meter above sea level. The study was conducted April until June 2009. The research was using Randomized Block Design with three repetitions. Treatment tested in this study were consist of: Without PGR (P0); Rootone F 1.2 g l-1 (P1); Rootone F 2.4 g l-1 (P2); Rootone F 3.6 g l-1 (P3); young coconut water 375 ml l-1 (P4); young coconut water 250 ml l-1 (P5); young coconut water 125 ml l-1 (P6); cow urine 150 ml l-1 (P7); cow urine 100 ml l-1 (P8); cow urine 50 ml l1 (P9). The result showed that every treatment had percentage 100% of shoot cutting which was having root formation, except treatment of Rootone F 1.2 g l-1 (P1) and without plant growth regulator (P0) which only got 86.67%. The number of root in treatment young coconut water 125 ml l-1 (P6) 23.17 was not significant different compared with young coconut water 375 ml l-1 (P4). The root length had a high value 2.76 cm by using Rootone F 3.6 g l-1 (P3). Treatment young coconut water 250 ml l-1 (P5) had the high value than the other treatments on variable length of stem, leaf area, number of leaves, flower initiation, and number of flowers.